2016
DOI: 10.1074/mcp.m115.056911
|View full text |Cite
|
Sign up to set email alerts
|

CONSTANd : A Normalization Method for Isobaric Labeled Spectra by Constrained Optimization

Abstract: In quantitative proteomics applications, the use of isobaric labels is a very popular concept as they allow for multiplexing, such that peptides from multiple biological samples are quantified simultaneously in one mass spectrometry experiment. Although this multiplexing allows that peptide intensities are affected by the same amount of instrument variability, systematic effects during sample preparation can also introduce a bias in the quantitation measurements. Therefore, normalization methods are required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…They reported that their method gave more precise estimates of protein abundance, and subsequently applied this normalization approach in a wide scale plasma proteomics study of nutrition . Similarly, although not demonstrated with plasma proteomics, Maes and co‐workers presented a normalization method for isobaric labeling that does not require a reference sample . To our knowledge no direct comparison has been made between the relative performances of these methods, although it could be viable to reanalyze and compare data from studies made with a pooled reference with the results using normalization derived from a data driven approach.…”
Section: Methodsologymentioning
confidence: 99%
“…They reported that their method gave more precise estimates of protein abundance, and subsequently applied this normalization approach in a wide scale plasma proteomics study of nutrition . Similarly, although not demonstrated with plasma proteomics, Maes and co‐workers presented a normalization method for isobaric labeling that does not require a reference sample . To our knowledge no direct comparison has been made between the relative performances of these methods, although it could be viable to reanalyze and compare data from studies made with a pooled reference with the results using normalization derived from a data driven approach.…”
Section: Methodsologymentioning
confidence: 99%
“…Another alternative to the use of SIL standards is to tag directly the tryptic peptides present in different samples with isobaric tags. These tags have a constant overall mass, so that the final mass of the same tryptic peptides present in different samples is still identical and will elute together in the LC‐MS analysis after sample mixing . The isotopic composition of the component parts of such tags is different, so different MS/MS fragments are observed for each chromatographic peak, which correspond to each sample analyzed.…”
Section: Non‐isotope Labeled Standardization Approachesmentioning
confidence: 99%
“…In the use of isobaric tags, one of the main issues to take care of is the potential errors or effects that might happen during sample preparation, and separations that can affect the quality and validity of the MS/MS quantitative results. These effects can be corrected via statistical approaches or normalization methods of the measured experimental peptides intensities by resorting to constrained optimizations and taking into account information about the labeling strategy …”
Section: Non‐isotope Labeled Standardization Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides procedures for recovering missing values, normalization is another important step in isobaric labeling-based quantification. For removing batch effects, several useful normalization methods have recently been developed [21][22][23][24][25][26][27] . Almost all of the methods are applying corrections at the level of protein quantification.…”
mentioning
confidence: 99%